Staying with the “trouble”: researching dystopias at the end of the world - Marques, Henrique Rodrigues (Revista do Colóquio, 2025)
This article proposes a reflection on the process of researching Cinema, Art and Culture in times of disaster in the Anthropocene. Starting from a research on speculative fiction in contemporary Brazilian queer cinema, I construct a tentacular thought through the creation of interdisciplinary kinship between different concepts such as Chthulucene (Haraway), failure (Halberstam), scholarship of fiction (Le Guin), political vernaculars (Macharia) and queer futurity (Muñoz).